Should the Philippine Government Support Washington's War in Iraq? - Banlaoi, Rommel C.; Simbulan, Roland G.; Aquino, Belinda A.; Baviera, Aileen; Quilop, Raymund Jose G. (Kasarinlan: Philippine Journal of Third World Studies; Vol 18 No 1 (2003): The World After 9.11, 2007)
Perspectives on "Should the Philippine Government Support Washington's War in Iraq?"
Keywords: Philippines; war on terror; Iraq; United States